2016
DOI: 10.1158/0008-5472.can-16-0361
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 Viral Factor HBZ Induces CCR4 to Promote T-cell Migration and Proliferation

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) causes adult T-cell leukemia-lymphoma (ATL) and other inflammatory diseases in infected individuals. However, a complete understanding of how HTLV-1 transforms T cells is lacking. Expression of the chemokine receptor CCR4 on ATL cells and HTLV-1-infected cells suggested the hypothesis that CCR4 may mediate features of ATL and inflammatory diseases caused by HTLV-1. In this study, we show that the constitutively expressed HTLV-1 bZIP factor (HBZ) encoded by HTLV-1 is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 46 publications
2
63
0
Order By: Relevance
“…Several mechanisms were identified for proliferation induced by HBZ [20, 2631]. However, it remains unknown how HTLV-1 induces T-cell specific proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Several mechanisms were identified for proliferation induced by HBZ [20, 2631]. However, it remains unknown how HTLV-1 induces T-cell specific proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Authors suggested that CCL22 could be a major factor of target cell attraction, as infected cells express CCR4. However, a recent study demonstrated that CCR4 expression can be induced on infection and HBZ expression, hence it may not be initially expressed on target cells46. In contrast, BLT-1, the high-affinity LTB4 receptor, is expressed in a variety of inflammatory and immune cells, including macrophages, activated CD4 T cells, effector CD8 T cells and dendritic cells27.…”
Section: Discussionmentioning
confidence: 99%
“…This cell-type specific expression of HBZ has been shown to play a variety of roles in the pathogenesis of HTLV-mediated T-cell leukemia (reviewed in [3, 26]). For instance, HBZ transforms T-cells into a cancerous phenotype, in part by enhancing the expression of chemokine receptor CCR4 in this cell type, which promotes T-cell proliferation and migration [27]. HBZ also inhibits HTLV-1 sense transcription by recruiting essential transcription factors, such as CREB, away from the proviral sense promoter – this process facilitates HTLV-1 latency in infected T cells [3].…”
Section: Antisense Transcription Among Exogenous Retrovirusesmentioning
confidence: 99%